The Prevalence of Stress and Its Possible Association with Demographic Features: A Cross Sectional Study - Dhiraj Kumar Srivastava (Journal of Medical Education, 2019)
Background: Medical professionals are prone to different forms of stress. These stresses start right from the beginning of medical professions. Most of the time such stresses have a negative impact on the psychological and physiological health. Objectives: To assess the prevalence of stress among medical students. To identify the possible stressors in medical students. Methods: The present study was a cross-sectional one carried out for a period of one month in Nov 2017 among medical students of 6th & 7th semesters. Assessment of stress was done using Medical Student Stress Questionnaire (MSSQ).The test of association was applied between the level of stress and sociodemographic profile of the participants. Result: A total of 122 students participated in the study. The prevalence of moderate to severe stress was 55.7%. It was more in female students compared with their male counterparts. There was no statistically significant difference in the levels of stress between male and female students among different stressors. Statistically significant association was noted between Academic Related Stressor and sex of the participants and fathers’ occupation. Significant association was also noted between Teaching and Learning Related Stressor and fathers’ occupation. Reliability analysis showed that overall Cronbach’s alpha for MSSQ for Indian students was 0.907. Conclusion: Moderate to severe stress is common among medical students and more common in female students. Most common source of these stresses is academic related issues. Fathers’ occupation is also a potential source of stress. Keywords: PSYCHOLOGICAL STRESS, DEMOGRAPHIC FACTOR, MEDICAL STUDENTS